Factors affecting the profitability of Malaysian commercial banks: an empirical evidence from the top three Malaysian banks / Muhammad Shazani Zamir Md Zamri - Md Zamri, Muhammad Shazani Zamir (2022)
First of most, banking sector is the backbone for a country's economy as banks performance can generate spill over impacts on different sectors (UNDP, 2009). The commercial banking industry of Malaysia is developing rapidly and has been acted as one ofthe critical diving forces of economy growth of the country. According to Abdul Jamal, Abdul Karim & Hamidi (2012), until 2011, commercial banks account the bulk of RMI, 7138.3 trillion assets and they represent the largest segment of all financial institutions in Malaysia. Therefore, this research is only focused on commercial banks since they are the largest fund provider in a country. The purpose of this research paper is to investigate the factors that influence bank profitability (ROA). The three factors are the cost-to-income ratio, consumer price index, and GDP growth Three Malaysian commercial banks have been chosen to represent the country's commercial banks. This project runs from 2011 to 2020 and data is collected on an annual basis. The data has been statistically analysed using descriptive statistics and multiple regression analysis. The results stated that bank size, liquidity and deposit ratio had a significant and positive relation with return on asset (ROA) except for GDP is significant but negative relationship. Although there were relationships among bank size, liquidity and deposit ratio but inflation rate did not have a significant influence on the profitability of the banks. The importance of the study is to improve the financial performance of Malaysian banking for investment and finance and to improve the Malaysia banks' operations.